PENGARUH DOSIS PUPUK KASCING DAN JENIS TANAMAN INANG TERHADAP PERTUMBUHAN BIBIT CENDANA (Santalum album L.) - I Made Mursedana (Agriculture Faculty of Flores University, 2014)
This study aims at investigating the impact of casting fertilizer dose and Host plant on the growth of Cendana Seed. The test design used was complete block random design with two factors of treatment that arranged in factorial. Both of the treatments are kascing fertilizer dose (0 g, 4 g, 8 g and 12 g-1) and Host Plant (without Host Plant, Suruhan, Krokot, and Kembang Siang).The pot used was Polybag (20 cm x 14 cm x 0,5 mm). All treatments were repeated three times and 240 pots were used. The result of the study shows that interaction between Kuscing fertilizer dose and kind of Host plant did not have a real impact on the growth of Cendana seed, instead of having a real impact on the ratio of root fertilizer, seed fresh weight, dry weight of oven seed, reserves of N, P, and K of plant, N total of land, C land organic, C/N ratio of land, the available P, the available and degree of land water. The highest of seed fresh weight was 4,0630 g in dose treatment 0 g Kascing fertilizer with Krokot Host plant and the highest of the oven-dry weight of seed was 1,8023 g in dose treatment of 4 grams Kuscing fertilizer with KrokotInang plant. The impact of Kuscing fertilizer apparently did not have real influence on all variables of Cendana seed growth. It may influence the variables of Cendana seed growth ageing around 30, 45, 60, 75, 90,105 and 120 days after weaning, except the diameter of seeds ageing 30 days after weaning had no real differences.